Characterization of organic constituents in waters and wastewaters of the Athabasca oil sands mining area - Strosher, M. T.; Peake, E. (1978)
The organic constituents of wastewaters discharged from the Great Canadian Oil Sands Ltd. (GCOS) plant and the Syncrude Canada Ltd. lease No. 17 were characterized and compared to those occurring naturally in the Athabasca River. Of the 16 chemical groups investigated in samples of upgrading plant effluent, coke storage area runoff, and Syncrude Canada Ltd. mine depressurization waters, the hydrocarbons, organic sulphur compounds, organic nitrogen compounds, and oxygenated organic compounds were found to be the most abundant constituents. Upgrading plant effluents contained an average of 36 mg/l of organic carbon, of which 17 mg/l was extractable with organic solvents. Organic sulphur compounds comprised 24% of the extractable organic carbon, oxygenated compounds 17%, hydrocarbons 16%, asphaltenes 10%, and nitrogen compounds 7%. Coke storage runoff revealed a total organic carbon content of 25 mg/l, 15 mg/l of which was extractable carbon. The extractable portion contained 18% asphaltenes, 13% oxygenated compounds, 11% sulphur compounds, 2% nitrogen compounds, and 1% hydrocarbons. Mine depressurization waters averaged 30 mg/l total organic carbon, 62% of which was extractable. Oxygen-containing compounds were the major contributors to the extractable fraction at 24%, with lesser contributions from sulphur compounds at 15%, asphaltenes 14%, nitrogen compounds 2%, and hydrocarbons 1%. Waters of the Athabasca River upstream from the GCOS plant contained only 13 mg/l total organic carbon, of which 4 mg/l was extractable. The major component of the extractable carbon, 29%, occurred as polar compounds. The hydrocarbon content was low, 0.8% of the extractable carbon, comparable to amounts founds in the mine depressurization waters, but far less than the 16% found in upgrading plant effluents. Under ice conditions on the Athabasca River, the chemical composition of the hydrocarbons 10 km downstream was directly comparable to those found in the upgrading plant effluent, diluted 70-fold. Initial investigations of bottom ...